PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ISPRING PADA MATERI ANALYTICAL EXPOSITION TEXT - Afidah, Nurul; Wulandari, Silvia (JoEMS (Journal of Education and Management Studies), 2021)
The present study aimed at developing learning media based on ICT (information and communication technology). In this case, the researchers used Ispring application, and the topic disscussed only covered Analytical exposition Text. ADDIE model that covered analyze, design, develop, implement,and evaluation was adapted in this study.Based on the result of develop phase, the mean score of media and material aspect were 3,93 and 3.76. It means that, the product was good enough and ready to implement. This product developed is far for being perfect. The next researcher may conducted similar study in different topic, skill,or level.